Pengaruh Debt to Equity Rasio dan Return on Asset terhadap Harga Saham pada PT Mustika Ratu Tbk Tahun 2015-2021 - Devitri Salsa Ashiva; Kristiana Sri Utami (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to analyze how much influence DER and ROA simultaneously and partially have on the Share Price of the Mustika Ratu Tbk company listed on the Indonesia Stock Exchange from 2015 to 2021. The F test shows that company performance measured by DER and ROA has no significant effect on Stock Price. The t test concluded that the DER variable had no significant effect on the stock price, but the ROA variable had a significant effect on the stock price. Based on the coefficient of determination test, the independent variable affects the dependent variable by 60.9% and there are still 39.1% explained by other factors not included in the study.